Effects of a visual‐feedback LED pacing system in middle-distance pool freestyle swimming - Chen, Zulin; Lin, Lihan; He, Yuqi; Zheng, Yikun; Zhang, Weiwei; Yan, Dingtao; Luo, Shumin; Chen, Huangtao; Chen, Hongmiao (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveThis study examined the effects of an intelligent LED pacing system with visual feedback on training performance and physiological responses in middle-distance freestyle swimming.MethodsTwelve high-level swimmers completed two 200 m freestyle trials in a self-controlled design: first a self-paced swim, followed 24 h later by an LED-paced swim. The LED system (Chaser-S1, Huaqiao University) converted individualized target times from each swimmer’s personal best into underwater light signals, providing real-time feedback. Trials were conducted in a 50 m indoor pool under standardized conditions. Each race was timed by three referees with synchronized stopwatches, heart rate was monitored with a Polar H10 under the swim cap, and fingertip blood lactate was sampled 1 min before and after each trial. Recorded outcomes included entire and segmental times, coefficient of variation (CV) of split time, blood lactate change (Δ mmol·L−1), heart rate range, and normalized HR range (HR CV). Normality was tested (Shapiro–Wilk), and paired-sample t-tests with Bonferroni adjustment (adjusted α = 0.01) were applied. Results included t values, P values, 95% confidence intervals, and effect sizes (Cohen’s d).ResultsLED pacing showed no significant differences in entire 200 m time or split times compared with self-pacing (entire: 150.21 ± 18.44 vs. 153.78 ± 20.26 s, d = 0.185; P = 0.014, not significant after Bonferroni adjustment). Pacing stability, assessed by CV of split times, showed no significant difference between LED pacing (8.49% ± 2.82%) and self-pacing (8.48% ± 2.56%) conditions (P = 0.981, d = 0.004). Physiologically, LED pacing lowered blood lactate accumulation (Δ lactate: 7.18 ± 1.61 vs. 8.63 ± 1.19 mmol L−1, P = 0.028, d = 1.019), smaller heart rate fluctuations (overall range: 45.50 ± 7.40 vs. 53.67 ± 7.75 bpm, P < 0.001, d = 1.078), and reduced HR CV across all segments (overall HR CV: 27.18% ± 4.46% vs. 32.51% ± 5.07, P < 0.001, d = 1.117).ConclusionIn highly trained swimmers, LED pacing exerted negligible effects on pacing consistency and race time but was associated with reduced post-exercise blood lactate and heart rate fluctuations, indicating potential utility for training load management rather than immediate performance enhancement.